2013
DOI: 10.2169/internalmedicine.52.8594
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Metastatic Leiomyosarcoma of the Pancreas: A First Case Report and Review of the Literature

Abstract: A 60-year-old woman was referred to our hospital with swelling of the right leg. After surgery, leiomyosarcoma of the right leg was diagnosed. Computed tomography showed two hypovascular masses in the pancreatic body and tail that were heterogeneously enhanced compared with the pancreatic parenchyma. On endoscopic ultrasonography, the tumors in the pancreatic body and tail both exhibited regular margins and were visualized as well-circumscribed masses with uneven interiors. Distal pancreatectomy was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Although primary pulmonary LMS are rare [3], pulmonary or bone metastases are a frequent finding in affected patients [4]. A typical feature of LMS is the long latency of metastatic lesions after resection of the primary tumor [5,6]. LMS manifestation in the pancreas is extremely rare and has only been reported in few cases and series up to now (▶ Table 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Although primary pulmonary LMS are rare [3], pulmonary or bone metastases are a frequent finding in affected patients [4]. A typical feature of LMS is the long latency of metastatic lesions after resection of the primary tumor [5,6]. LMS manifestation in the pancreas is extremely rare and has only been reported in few cases and series up to now (▶ Table 1, 2).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, metastatic leiomyosarcoma isolated to the pancreas from a distant primary tumor site is extremely rare [27]. …”
Section: Discussionmentioning
confidence: 99%
“…A case of pancreatic metastasis from a uterine LMS is rare [28,29]. Ogura et al identified, in a literature review, 25 cases of LMS metastases to the pancreas, of which 7 cases were from a primary uterine tumor [30].…”
Section: Discussionmentioning
confidence: 99%